Design of photovoltaic-thermal (PVT) platform - Teo, Wei Xiang (Nanyang Technological University, 2023)
As the world starts running out of fossil fuel, renewal energy has been becoming increasingly popular. Solar energy is a type of renewable energy that comes from the sun. It is a clean and sustainable source of energy that can be harnessed using different technologies to generate electricity, heat water, or power devices. Photovoltaic (PV) panels have been adopted for direct solar energy to electricity conversion. However, not all solar energy entering the PV Panel is converted into electrical energy. Under standard operating conditions, the solar to electricity conversion efficiency of typical commercial PV panels built with silicon-based PV Cells is around 20%. Most of the remaining solar energy is retained as residual solar thermal heat in the PV panels, thus increasing the temperature of PV cells. Higher PV panel temperature can negatively impact the solar-to-electricity conversion efficiency of the PV cells in the PV panels. The PV panel efficiency typically drops about 3.8% for every 10 oC increase in temperature. The aim of this project is to develop an add-on PV cooling design that can be applied to existing PV installations to reduce the temperature of PV panels under sunlight and enhance the overall solar to electricity conversion efficiency of the PV installation. Computational Fluid Dynamics (CFD) Simulation was carried out using commercially available software ANSYS FLUENT to investigate the effectiveness of the design. The proposed PV panel cooling design can used to cool the PV panels of the PV Panel installations on the roof top Housing Development Board (HDB) residential buildings under the Singapore Government SolarNova programme to install up to 3GWp PV panels by 2030 in HDB blocks. The hot water after harvesting the residual solar thermal heat in the PV panels used in this design can be stored and supplied to the HDB households for domestic warm water applications. The ANSYS CFD simulation showed that the proposed PV panel cooling design can effectively cool down the PV panels, but the temperature of the heated cooling water produced in the proposed design is not hot enough to be used for household direct domestic warn water usage due to not so effective solar thermal harvesting from the PV panels in the proposed design and additional heating (electric) is required. The project can be further validated by running an actual physical prototype in the future.